Inkubator Bisnis Halua Tradisional: Inovasi Kewirausahaan Digital Generasi Muda Berbasis Kearifan Lokal - Bangun, Kristina; Elisabeth Simangunsong; Darna Sitanggang (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
This traditional halua business incubator activity aims to develop entrepreneurial innovation based on halua traditional culinary products, supported by digital entrepreneurship for the younger generation. The partner of this program is the micro, small, and medium enterprise (MSME) Rumah Manis Kasih Ibu, which specializes in the production of halua sweets based on local wisdom. The main problems faced by the partner include limited innovation in digital marketing, lack of simple financial management, and the absence of business development strategies oriented toward the younger generation. The implementation methods consist of several stages, namely preparation, socialization, digital entrepreneurship training, application of simple financial recording tools, mentoring on social media-based promotion, and evaluation. The results of the activity show improvements in the partner’s business management skills, enhancement of halua product quality through standardized operating procedures (SOPs), and mastery of digital media as a marketing tool. This program is expected to serve as a model of a traditional culinary business incubator that can be replicated by other MSMEs to strengthen economic independence based on local culture.